Analysis of the AUKUS Agreement on Security in the South China Sea Region - Sumadinata, Widya Setiabudi (International Publisher (YAPENBI), 2022)
Rich in natural oil and gas resources, the South China Sea region is one of the busiest shipping zones in the world. This area has been claimed by China as its sovereign territory, prompting protests from Vietnam and the Philippines, among others. This makes this region extremely conflict-prone. The existence of this possible war has prompted the United States to compete with China for influence in this region, rather than remaining mute. The United States, Britain, and Australia created the AUKUS Security Treaty to increase their power. Therefore, the purpose of this study is to assess the AUKUS security treaty for the South China Sea region. This study employs a qualitative methodology with descriptive techniques. Geopolitical dynamics have resulted in competition for supremacy in the South China Sea Region, according to the findings of this study. This has an effect on the region's security vulnerabilities. The formation of the AUKUS Pact was motivated by the need to reduce Chinese dominance in the South China Sea region. The inability of countries in the South China Sea region to sustain security stability in the region is a result of their contradictory traits. The author says that countries in the South China Sea region, particularly ASEAN members, have two options for sustaining security stability in the region: power balancing or diminishing China's dominance by backing the AUKUS Pact.